Comparison of the protective effects of insulin and saponin on renal ischemia-reperfusion injury - Fardin Rezaei; Mohammad Ghasem Golmohammadi; Hakimeh Saadati; Shokofeh Banaei (Shahrekord University of Medical Sciences, 2024)
Introduction: Oxidative stress induced by renal ischemia-reperfusion (IR) is an effective element in the pathophysiologic renal alterations generated during IR injury. This investigation intended to study the effects of saponin (SP) and insulin (INS) in kidney IR injury. Methods: Wistar male rats were assigned into four groups: the control, IR, SP + IR, and INS + IR. The rats were nephrectomized unilaterally and went under 45 minutes ischemia followed by 24-hour reperfusion. SP (2.5 mg/kg) and INS (30 U/kg) were intraperitoneally injected prior to ischemia. Following the treatment, a blood sample was taken for the measurement of biochemical parameters, and the left kidney was taken out for the determination of oxidative stress markers and histological changes. Results: Blood urea nitrogen (BUN), creatinine (Cr), malondialdehyde (MDA) levels, and histopathological scores significantly increased by kidney IR while antioxidant enzymes were significantly decreased. However, the administration of SP and INS significantly decreased BUN, Cr, MDA, and histological scores and improved the antioxidant defense system. Conclusion: SP and INS exert nephroprotective effects against oxidative damage caused by IR. It seems that SP has a renoprotection similar to INS in renal IR.